1993
DOI: 10.1111/j.1440-1681.1993.tb01654.x
|View full text |Cite
|
Sign up to set email alerts
|

The Marine Natural Product 3,5‐dibromo‐2‐(2,4‐dibromo‐phenoxy)phenol, Inhibits Contractile Activity in the Guinea‐pig Ileum

Abstract: 1. The tetrabrominated diphenyl ether 3,5-dibromo-2-(2,4-dibromophenoxy)phenol (BPE), a natural marine product isolated from a sponge, was tested for pharmacological activity in guinea-pig ileum. 2. BPE (2 mumol/L) decreased basal force and the frequency of spontaneous contractions of the ileum. It also significantly decreased contractions of the ileum induced by 5 mmol/L barium and to electrical stimulation at parameters which stimulated intrinsic nerves. 3. The slopes of concentration-response curves to acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Morphological evidence previously indicated that most deep-sea genera are ubiquitous and benthic community assemblages are similar worldwide [18], although a number of novel deep-sea genera had been identified [19-21]. Within our dataset, deep-sea specimens comprised a taxonomically diverse group of genera representing every major phylogenetic lineage in the Enoplida (Figure 1).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Morphological evidence previously indicated that most deep-sea genera are ubiquitous and benthic community assemblages are similar worldwide [18], although a number of novel deep-sea genera had been identified [19-21]. Within our dataset, deep-sea specimens comprised a taxonomically diverse group of genera representing every major phylogenetic lineage in the Enoplida (Figure 1).…”
Section: Discussionmentioning
confidence: 85%
“…This genus does not appear to have any recent shallow-water relatives in molecular phylogenies and appears to have split off early from other genera within the Enchelidiidae (Clade IIa, Figure 1); more extensive sampling is needed to further elucidate generic relationships within this family. Similarly, the genus Cricohalalaimus (Clade IIIc, Figure 1) has only been described from deep-sea sediments [19]-- molecular evidence indicates that this taxon represents a divergent lineage that is most closely related to genera Thalassoalaimus and Litinium (SSU and LSU support values >98%), even though the distinct morphology of Cricohalalaimus does not intuitively suggest a relationship with either group.…”
Section: Discussionmentioning
confidence: 99%
“…Many other peptides with biological activity have been isolated from sponges, but as far as we know, no calcium channel effectors have been described until now. A previous report has shown that sponge extracts are able to block carbachol-induced contractions in intestinal smooth muscle, which are insensitive to dihydropyridines (21). These observations suggest that these organisms could synthesize calcium channel effectors.…”
mentioning
confidence: 70%
“…2) disruptions of calcium homeostasis/signaling as shown in one of the earliest mechanistic studies of PBDEs (26) and more recently demonstrated in several cell types including human neuronal precursors (27,28); 3) toxicity produced by mitochondrial disruptions including uncoupling of oxidative phosphorylation (29) and subsequent elevated production of reactive oxygen species (ROS) which can lead to DNA damage and apoptosis; 4) dysregulation of epigenetic mechanisms including DNA methylation, chromatin dynamics, and non-coding RNAs--an emerging point of investigation that we have recently reviewed (30). It is possible that one or more of these molecular mechanisms contribute to exposure-related behavioral abnormalities; however, the extent of their involvement, if any, remains unclear.…”
Section: Introductionmentioning
confidence: 99%